MicroRNA-486-5p Suppresses Lung Cancer via Downregulating mTOR Signaling In Vitro and In Vivo - Ding, Lei; Tian, Wu; Zhang, Hui; Li, Wanqiu; Ji, Chunyu; Wang, Yuanyuan; Li, Yanli (Frontiers in Oncology, 2021)
Lung cancer is one of the central causes of tumor-related deaths globally, of which non-small cell lung cancer (NSCLC) takes up about 85%. As key regulators of various biological processes, microRNAs (miRNAs) have been verified as crucial factors in NSCLC. To elucidate the role of miR-486-5p in the mTOR pathway, we investigated its role in NSCLC and related signaling. Our results confirmed that miR-486-5p was downregulated in most of human NSCLC tissue samples and cell lines. Further study confirmed that it inhibited NSCLC through repression of the mTOR pathway via targeting both ribosomal proteins S6 kinase A1 (RPS6KA1, RSK) and ribosomal proteins S6 kinase B1 (RPS6KB1, p70S6K), which are critical components of the mTOR signaling. Additionally, miR-486-5p impeded tumor growth in vivo and inhibited tumor metastasis through repression of the epithelial-mesenchymal transition (EMT). Taken together, our study verified the role that miR-486-5p exerts in NSCLC, and its expression pattern in the different stages and morphologies of NSCLC makes it a promising biomarker in the early diagnosis of the disease.